Factors contribute to workplace happiness among support service employees in KPJ Puteri Specialist Hospital / Nur Zafirah Ahmadi - Ahmadi, Nur Zafirah (Faculty of Business and Management, 2020)
The study explores the factors that contribute to workplace among support service employees at KPJ Puteri Specialist Hospital. The purpose of this study is to determine the relationship between friends’ factor and workplace happiness and also to determine the relationship between employee engagement and workplace happiness. The variables that are being used in this study are friends’ factor and employee engagement. The sampling technique that was used in this study is convenience sampling. The questionnaire was distributed to the support service employees and data has been analyzed through the Statistical Package for Social Sciences (SPSS). The findings show that there is a significant relationship between friends’ factor and workplace happiness. The result for employee engagement is shows that there is a significant relationship between employee engagement and workplace happiness